## Hiiii guys Plz Answer fast (xa/xb)a²+2ab+b²×(xb/xc)×b²+2bc+c²×(xa/xc)c²+2ca+a² ​

Question

Hiiii guys

(xa/xb)a²+2ab+b²×(xb/xc)×b²+2bc+c²×(xa/xc)c²+2ca+a²

in progress 0
1 month 2021-08-18T08:52:26+00:00 2 Answers 0 views 0

1. Step-by-step explanation:

(xbxa)a2+ab+b2

\times \left(\frac{x^{b}}{x^{c}}\right)^{b^{2}+bc+c^{2}}×(xcxb)b2+bc+c2

\times \left(\frac{x^{c}}{x^{a}}\right)^{c^{2}+ca+a^{2}}×(xaxc)c2+ca+a2

=\left(x^{a-b}\right)^{(a^{2}+ab+b^{2})} \times(xa−b)(a2+ab+b2)×

\left(x^{b-c}\right)^{(b^{2}+bc+c^{2})}(xb−c)(b2+bc+c2)

\times \left(x^{c-a}\right)^{(c^{2}+ca+a^{2})}×(xc−a)(c2+ca+a2)

=x^{(a-b)(a^{2}+ab+b^{2})}=x(a−b)(a2+ab+b2)

\times x^{(b-c)(b^{2}+bc+c^{2})}×x(b−c)(b2+bc+c2)

\times x^{(c-a)(c^{2}+ca+a^{2})}×x(c−a)(c2+ca+a2)

=x^{a^{3}-b^{3}}\times x^{b^{3}-c^{3}}\times x^{c^{3}-a^{3}}=xa3−b3×xb3−c3×xc3−a3

=x^{a^{3}-b^{3}+b^{3}-c^{3}+c^{3}-a^{3}}=xa3−b3+b3−c3+c3−a3

=x^{0}=x0

= 1=1

Therefore,

\left(\frac{x^{a}}{x^{b}}\right)^{a^{2}+ab+b^{2}}(xbxa)a2+ab+b2 \times \left(\frac{x^{b}}{x^{c}}\right)^{b^{2}+bc+c^{2}} \times \left(\frac{x^{c}}{x^{a}}\right)^{c^{2}+ca+a^{2}}×(xcxb)b2+bc+c2×(xaxc)c2+ca+a2 = 1